1984
DOI: 10.1113/jphysiol.1984.sp015258
|View full text |Cite
|
Sign up to set email alerts
|

Reversal by angiotensins II and III of the effects of converting enzyme inhibition on renal electrolyte excretion in rats.

Abstract: SUMMARY1. Experiments were carried out in anaesthetized rats to compare the abilities of angiotensin II (A II) and angiotensin III (A III) to reverse the effects of angiotensin converting enzyme inhibition (Teprotide) on salt and water excretion.2. In rats infused with Teprotide, significant increases in urine flow and sodium excretion were observed and arterial blood pressure decreased. Addition of A II (10 pmol min-) to the Teprotide infusion reduced renal excretion of sodium and water to control values and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…Our earlier study [16] demonstrated that ICV administration of ANG III induced diuretic and natriuretic effects in conscious rats. Similar renal actions of ANG II and III have been reported when these peptides are given intravenously [17][18][19]. These observations are compatible with the notion that central ANG II and III may be similar to the well-known peripheral ANG peptides playing an important role in the regulation of body fluid and cardiovascular function.…”
supporting
confidence: 78%
“…Our earlier study [16] demonstrated that ICV administration of ANG III induced diuretic and natriuretic effects in conscious rats. Similar renal actions of ANG II and III have been reported when these peptides are given intravenously [17][18][19]. These observations are compatible with the notion that central ANG II and III may be similar to the well-known peripheral ANG peptides playing an important role in the regulation of body fluid and cardiovascular function.…”
supporting
confidence: 78%
“…First, studies of the actions of ANG III (des-Asp 1 -ANG II) in the rat (29,32) and in anesthetized dogs (11,24) indicate that infusion of ANG III might produce vasoconstriction, sodium retention, and aldosterone release. This response is thought to be similar to ANG II, although not as potent.…”
mentioning
confidence: 99%
“…(1975) showed that All and All1 were equipotcnt in their ability to suppress renin release in the dog, while Naftilan and Oparil(1978) found thai A11 was more potent than AIII in suppressing renin release in vitro. In separate studies, A11 and All1 had been shown to be equipotent in their abilities to reverse the natriuretic and diuretic effects of angiotensin converting enzyme inhibition (Harris & Munro 1984). The physiological role of endogenous A111 and its relative potency compared with All in control ofrenin release awaits more detailed dose-response studies.…”
Section: Discussionmentioning
confidence: 99%
“…1978) have shown that inhibition of renin secretion may be mediated by the macula densa and dependent on presentation of NaCl to the distal tubule (Briggs & Schnermann 1986). Angiotensin converting enLyme inhibitors are natriuretic in the rat (Harris & Munro 1984) and hence may modulate renin release by altering sodium balance. Therefore to examine whether captopril-induced changes in electrolyte excretion are involved in captopril-induced renin release the effect ofcaptopril on renin release from animals whose kidneys have been rendered non-filtering by bilateral ureteric ligation has been examined (Blaine et al 1970;Nascimento et a/.…”
Section: Introductionmentioning
confidence: 99%